Increasing retirement savings through access points and persuasive messages: Evidence from Mexico - Mariano Bosch Mossi; Adrian Rubli (Inter-American Development Bank (IDB), 2019)
Transaction costs impose a barrier to savings, but lowering them may have smaller impacts than expected due to other constraints, such as psychological biases. Within the context of retirement savings under defined contributions in the privatized pension system in Mexico, we analyze two staggered policies: an expansion of access channels for additional contributions through 7-Eleven stores, and the bundling of this policy with a media campaign providing persuasive reminders to save. We find that access alone has small and weak effects on savings, but including the persuasive message leads to a 10-12% increase in savings behavior that is long-lasting.
Keywords: D14; D83; G23; 330; retirement savings; access; transaction costs; media campaigns; non-branded advertising; persuasion